Does the Duration of Abdominal Pain Prior to Admission Influence the Severity of Acute Pancreatitis? - Kapoor, Karan; Repas, Kathryn; Singh, Vikesh K; Conwell, Darwin L; Mortele, Koenraad J; Wu, Bechien U; Banks, Peter A (JOP. Journal of the Pancreas, 2013)
Context In a prior report involving patients with hemoconcentration at admission, those with necrotizing pancreatitis presented significantly earlier than those with interstitial disease suggesting that duration of abdominal pain prior to presentation may have prognostic significance in acute pancreatitis. Objectives The aim of the present study was to determine whether the duration of abdominal pain prior to admission influences the severity of acute pancreatitis. Methods During a five-year period, all patients presenting directly to our hospital with their first episode of acute pancreatitis were enrolled in a cohort study. We analyzed data obtained from records of all such patients and performed a separate analysis on those with hemoconcentration (hematocrit equal to, or greater than, 44%) at presentation to determine whether duration of abdominal pain prior to presentation was associated with severity of acute pancreatitis. Duration of abdominal pain was categorized as persisting for either less than 12 h or 12 h or more prior to arrival. Prognostic markers of severity included admission hematocrit and blood urea nitrogen (BUN), as well as the development of systemic inflammatory response syndrome (SIRS) during the initial 24 h of hospitalization. Outcome measures included pancreatic necrosis based on contrast-enhanced CT scanning, need for intensive care, length of hospitalization, and death. Radiologic severity of peripancreatic inflammatory changes was assessed within 48 h of admission in accordance with the Balthazar-Ranson scoring system (A-E). Results Among a total of 318 patients, there were 62 (19.5%) with hemoconcentration at admission. Among the 318 patients, there was no significant difference in the prevalence of pancreatic necrosis when comparing the less than 12 h group to the 12 h or more group. Among the 62 patients with hemoconcentration, those admitted within 12 h compared to those admitted 12 h or more following the onset of abdominal pain had an increased radiologic severity of acute pancreatitis (Balthazar-Ranson grade D or E: 83.3% vs. 40.0%; P=0.006) and an increased prevalence of pancreatic necrosis (21.1% vs. 2.3%; P=0.028). Conclusion Duration of abdominal pain prior to admission impacts the severity of acute pancreatitis only among patients with hemoconcentration at presentation. Image: Selection of eligible patients with acute pancreatitis.